A bayesian via laplace approximation on log-gamma model with censored data - Yusuf, Madaki Umar; Abu Bakar, Mohd Rizam; Husain, Qasim Nasir; Ibrahim, Noor Akma; Arasan, Jayanthi (Canadian Center of Science and Education, 2016)
Log-gamma distribution is the extension of gamma distribution which is more flexible, versatile and provides a great fit to some skewed and censored data. Problem/Objective: In this paper we introduce a solution to closed forms of its survival function of the model which shows the suitability and flexibility towards modelling real life data.